Role of distributed/discrete solar heaters during natural convection in the square and triangular cavities: CFD and heatline simulations. (October 2016) - Das, Debayan; Basak, Tanmay
Highlights: Discrete solar heating vs. optimal thermal management is studied. Natural convection in the square and triangular enclosures is examined. Effect of various positioning of solar heaters is analyzed by heatline concept. Efficient heating strategy is based on the optimal positioning of solar heaters. Overall, thermal mixing within the triangular-type 2 enclosure is higher. Abstract: Solar heating has gained significant attention for various material processing applications and the current work focuses on the discrete solar heating of fluids involving natural convection heat transfer. Five different cases based on the heater location on the side walls of the square, triangular-type 1 and triangular-type 2 (inverted triangle) enclosures are studied. The mathematical tool of 'heatlines', which represents the trajectories of flow of heat is used to visualize the total energy flow in the domain. Galerkin finite element method with adaptive grids has been implemented for solving the governing equations of heat and fluid flow and Poisson-type of equations for solving the streamfunction and heatfunction. The local and average Nusselt numbers vs. average or cup mixing temperature have been evaluated. Based on the optimum thermal mixing and high temperature uniformity, the discrete solar heating strategy involving the positioning of the heaters near the bottom portion of the side walls and heaters along the central portion of the side walls were found to be energy efficient irrespective of any enclosure. The asymmetrically distributed heating strategy was also found to be suitable for the systems leading to the significant temperature uniformity over a larger region. Overall, the results displayed an increase in the mixing efficiency index for the square and triangular-type 2 (inverted triangle) enclosures in the presence of discrete solar heaters.